Research into spontaneous activity of myocardial cells under normal and pathological conditions using the hardware and software complex based on nanosensors; IOP Conference Series: Materials Science and Engineering; Vol. 457 : Modern Technologies for Non-Destructive Testing - Yuzhakov M. M. Mikhail Mikhaylovich; Ivanov M. L. Maxim Leonidovich; Turushev N. V. Nikita Vladimirovich; Maksimov I. V.; Mazikov S. V.; Kodermyatov R. E.; Wenjia G.; Zimin I. A. (2019, 2019)
Title screen